The impact of pronoun choices on consumer engagement actions: Exploring top global brands' social media communications - Labrecque, Lauren I.; Swani, Kunal; Stephen, Andrew T. (Psychology & marketing, 2020)
To enhance the understanding of consumer engagement with brand content on social media, this study examines how pronoun choices affect different types of consumer engagement (e.g., likes, comments, shares) by simultaneously exploring five different pronoun types (first‐person singular, first‐person plural, second person, third‐person singular, and third‐person plural). Furthermore, this study explores how the effects of these linguistic (pronoun) choices vary across two brand classifications: characteristics (hedonic vs. utilitarian) and offerings (goods vs. services). The proposed multivariate Poisson regression model, analyzing 15,788 unique brand posts from Facebook over an 8‐month period, reveals differences in engagement due to pronoun usage across brand classifications. These results offer a deeper understanding of how the way brands talk to consumers on social media platforms influences consumers' attitudes (likes), propensity to engage with the brand (comments), and willingness to share branded content with their social networks (shares) across different brand classifications.